Improvement on bioprocess economics for 2, 3-butanediol production from very high polarity cane sugar via optimisation of bioreactor operation. (February 2019) - Maina, Sofia; Stylianou, Eleni; Vogiatzi, Effrosyni; Vlysidis, Anestis; Mallouchos, Athanasios; Nychas, George-John E.; de Castro, Aline Machado; Dheskali, Endrit; Kookos, Ioannis K.; Koutinas, Apostolis
Graphical abstract: Highlights: Temperature, pH and kL a influence substantially BDO production. Optimisation of bioreactor operation led to enhanced BDO production efficiency. A productivity of 3.95 g L −1 h −1 was achieved at optimal bioreactor operation. The BDO minimum selling price is 3.12/kg at 10, 000 t annual production capacity. Abstract: This study focuses on the optimisation of 2, 3-butanediol (BDO) production in fed-batch cultures carried out with the bacterial strain Enterobacter ludwigii using very high polarity (VHP) sugar from sugarcane mills. Various kL a values were evaluated using either complex or synthetic fermentation media demonstrating that the latter enhance BDO production efficiency with low by-product formation. The pH (6.3) and temperature (33.9 °C) employed in fed-batch bioreactor cultures has been optimised via experimental design. Fed-batch cultures carried out at the optimum temperature and pH and varying kL a values resulted in BDO concentration, yield and productivity of 86.8 g/L, 0.37 g/g and 3.95 g L −1 h −1 . Using this fermentation efficiency, the minimum selling price of BDO for annual production capacities of 10, 000 t and 50, 000 t was estimated at 3.12/kg and 2.67/kg, respectively, for a VHP cane sugar market price of 0.4/kg.